PARTISIPASI PEREMPUAN DALAM PENDIDIKAN DI MASYARAKAT TIMUR TENGAH KUNO - Gernaida Krisna R. Pakpahan; Onnie Lumintang (Diegesis : Jurnal Teologi, 2024)
Women are always in a dilemma in the postmodern era. For those with a positive view, women are seen as having skills that men do not have. However, from the negative side, women are seen as inferior and weak. The feminist movement, which has spread to all levels of society, is also seen as the wrong response. Therefore, studies are needed that show women's education from ancient sources, namely the Ancient Middle East, which was the ancestor of Christianity, as the context for the birth of the religion of Israel. The research method used was descriptive qualitative. The research results show that women's participation in education in Ancient Middle Eastern society is evident. Even though they live in a patriarchal environment in Israel, women play a role in family, law, kinship, and religion in Ancient Middle Eastern society. The presence of women has colored the various roles of society at that time